2006
DOI: 10.1063/1.2180407
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric function and electric properties of germanium thin films prepared by gold mediated crystallization

Abstract: Crystallization of hydrogenated amorphous germanium (a-Ge:H) thin films deposited by plasma enhanced chemical vapor deposition using the GeH4 and H2 precursors has been investigated. A comparative analysis of the kinetics of the thermal crystallization by annealing to 650°C and of the gold-mediated crystallization (Au-MMC) is carried out. The impact of the Au-MMC on the microcrystalline Ge film microstructure and electrical properties is discussed. The Au thin layer results in a more dense and ordered structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…They attributed the conversion of conduction type to the formation of oxygen vacancy, which leaded to the pinning of E F near the valence bands. 16,19 But this is not the case in our samples. From the results of FTIR, no Ge-O bonds are found.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…They attributed the conversion of conduction type to the formation of oxygen vacancy, which leaded to the pinning of E F near the valence bands. 16,19 But this is not the case in our samples. From the results of FTIR, no Ge-O bonds are found.…”
Section: Resultscontrasting
confidence: 65%
“…19 Recently, Zhang et al 16 also reported that holes were the major carriers in ncGe films embedded in SiO 2 matrix according to Hall measurements and thermoelectric power results. They attributed the conversion of conduction type to the formation of oxygen vacancy, which leaded to the pinning of E F near the valence bands.…”
Section: Resultsmentioning
confidence: 96%
“…1. At first sight, the largest difference is a reduced intensity of the E 1 transitions, which is correlated to the nanocrystalline structure of the Ge layer [11][12][13][14]. To determine the volume fractions of crystallized and amorphous Ge in every sample it is necessary to use as input the characteristic ε of the components.…”
Section: Resultsmentioning
confidence: 99%
“…They are determined by minima of the second derivative of ε 2 [7][8][9]. In this case it is proper to use ε 2 dispersion obtained from wavelength by wavelength analysis because otherwise CPs positions could be imposed by the used dispersion model.…”
Section: Resultsmentioning
confidence: 99%
“…However, using optical constants of bulk Ge in EMA for characterization of a mixture containing Ge quantum dots can fail because the optical constants of dots can be quite different than those of material as bulk. Solutions proposed to solve this problem are finding volume fraction and optical constants of the quantum dots by direct inversion [6,7], using dispersion model [8] or using splines [9]. These approaches were applied always to the homogeneous thin films, where Ge was homogeneously distributed through the film.…”
Section: Introductionmentioning
confidence: 99%